The heart of everything the art and artists of Mornington & Bentinck Islands. - Evans, Nicholas (Fitzroy, Vic. McCulloch & McCulloch Australian Art Books, 2008)
Features the work of artists from Mornington Island Arts and Craft Centre.
Keywords: Art, Aboriginal Australian -- Australia -- Mornington Island (Qld.); Art, Aboriginal Australian -- Australia -- Betninck Island (Qld.); Artists, Aboriginal Australian -- Australia -- Bentinck Island (Qld.)